Revitalisasi Akal dalam Teologi Islam: Telaah Rasional atas Pemikiran Kalam Harun Nasution - Firdaus, Dadan; Adam Maulana, Iyadh; Hanifa, Alfira; Aura Pusparani, Syahla (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Harun Nasution’s theological thought represents a significant effort to revive the role of reason as a central element in understanding Islamic teachings. In the context of Islamic thought in Indonesia, which has long been dominated by traditional and textual approaches, Harun Nasution reintroduced a rational perspective rooted in the Mu‘tazilite theological legacy. Through his academic education at Al-Azhar University and McGill University, he developed a theological framework that emphasized intellectual freedom, rationality, and the historical relevance of Islam in facing modern challenges. This study aims to explain how the integration of reason into Islamic studies was realized through Nasution’s rational theological approach, using a library research method with historical and thematic approaches. The analysis focuses on the historical development of rational kalam, the position of reason within theological methodology, and the impact of his thought on the reform of modern Islamic education. The findings show that Harun Nasution’s rational approach not only shaped a new paradigm in theological studies but also opened space for dialogue between Islam and contemporary intellectual discourse. His ideas make a significant contribution to building a more contextual, critical, and open understanding of Islam in response to the advancement of knowledge and social change.